An Examination of Investigative Practices of Homicide Units in Florida. Issue 2 (May 2019) - Hough, Richard; McCorkle, Kimberly D.; Harper, Sarah
The study examined Florida law enforcement agency homicide investigation practices previously identified in the literature as best (or most frequent). Departments handling at least 25 homicides per year and those that handle fewer were surveyed, a comparison not previously examined. The agencies had similar clearance rates. Smaller agencies and those handling fewer homicides tended to use an outside agency for crime scene services, did not have a cold case function, were less likely to use a computerized case management system, and did not view public cooperation as a barrier to homicide investigations to the degree that larger agencies did.